Culture and Health: Recent Developments and Future Directions. (26th September 2021) - Miyamoto, Yuri; Ryff, Carol D.
Abstract: Evidence of cultural differences in relationships and emotions has accumulated over the past few decades. As findings on cultural differences in psychological processes have increased, there has been growing interest in investigating whether they have implications for other phenomena, such as health. Using scientific advances from the MIDUS and MIDJA studies, both publicly available, we examine links between culture and health. First, there is a brief review of the accumulated evidence on cultural influences on health correlates concerning psychosocial factors. We then feature two recent developments: a more micro‐level perspective regarding biological factors that may be involved in the culture and health linkage, and a more macro‐level view of socioeconomic inequality, which also concerns health. Both perspectives inform the pathways through which health effects become manifest. Finally, we conclude our review by highlighting the changing historical contexts within which these cross‐cultural investigations occur. Specifically, we draw attention to the widening of economic inequality across cultures and the world‐wide COVID‐19 pandemic. These instances bring notable implications for future research on health across cultural contexts.